Show Boat Based on a Novel by Edna Ferber - Kern, Jerome (Criterion, 2020)
Jerome Kern and Oscar Hammerstein II's immortal musical adaptation of Edna Ferber's sprawling novel receives its most faithful and enduring cinematic adaptation under the elegant direction of James Whale (Bride of Frankenstein). A rich portrait of changing American entertainment traditions and race relations, "Show Boat" spans four decades and three generations as it follows the fortunes of the stage-struck Magnolia, an aspiring actor whose journey takes her from her family's humble floating playhouse in the 1880s South to the height of fame in the 1930s North. The cast of show-business legends includes Helen Morgan (Applause), Hattie McDaniel (Gone with the Wind), Charles Winninger (Beyond Tomorrow), and the great Paul Robeson (The Emperor Jones), whose iconic, soul-shaking rendition of "Ol' Man River" is one of the crowning glories of the American stage and screen. [Cover]
Keywords: Blu-Ray-Disc